Persepsi Mahasiswa KPI UIKA Bogor Terhadap Program Radio Pro 2 RRI Bogor - Arraki, Muhammad Kholil (Komunika: Journal of Communication Science and Islamic Dakwah, 2021)
The purpose of this study was to determine the perception of KPI UIKA Bogor students towards the RRI Bogor Radio Pro 2 program and later in it would be known what points were the input for the programs in it. This research method uses quantitative methods, namely the method of distributing questionnaires to KPI UIKA Bogor students by using Suharsimi Arikunto's theory which takes a partial sample or representative of the population being studied. If the subject is less than 100, it is better to take all, on the contrary if the subject is greater than 100, it can be taken between 10-15%. The results obtained from the study were firstly the results of the research on the perception of UIKA KPI students on the satisfaction motive of the Pro 2 RRI Bogor program which got first place by getting a score of 550 from the results of the questionnaire answers, then the program effect dimension was ranked second with a score of 460 from the results of the questionnaire answers. In the third place, there is a motive for the respondents' knowledge of all programs in Pro 2 RRI Bogor with a score of 295. Finally, there is a motive for the general view of respondents on the Pro 2 RRI Radio Bogor which is ranked fourth with a score of 221. In general, the results obtained are known. that the listener's perception, namely the Islamic Broadcasting and Communications Students, University of Ibn Khaldun Bogor, is found in the satisfaction motive of the RRI Bogor Pro 2 Program. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui persepsi mahasiswa KPI UIKA Bogor terhadap program Radio Pro 2 RRI Bogor dan nantinya didalamnya akan di ketahui apa saja poin yang menjadi masukan untuk program-program didalamnya. Metode penelitian ini menggunakan metode kuantitatif yaitu dengan metode penyebaran angket kepada Mahasiswa KPI UIKA bogor dengan menggunakan teori Suharsimi Arikunto yang mengambil sempel sebagian atau wakil populasi yang diteliti. Apabila subyeknya kurang dari 100 lebih baik diambil semua, sebaliknya jika subyeknya lebih besar dari 100 dapat diambil antara 10-15%.Hasil yang diperoleh dari penelitian tersebut pertama hasil penelitian persepsi mahasiswa KPI UIKA terhadap motif kepuasan program Pro 2 RRI bogor mendapat peringkat pertama dengan mendapat skor 550 dari hasil jawaban kuesioner, Selanjutnya dimensi efek program menempati peringkat kedua dengan skor 460 dari hasil jawaban kuisoner, Kemudian di peringkat ketiga ada motif pengetahuan responden terhadap seluruh program-program yang ada di Pro 2 RRI Bogor dengan skor 295, Terakhir ada motif pandangan umum responden terhadap radio Pro 2 RRI Bogor yang mendapat peringkat keempat dengan skor 221. Secara umum, hasil penelitian yang diperoleh diketahui bahwa persepsi pendengar yaitu Mahasiswa Komunikasi dan Penyiaran Islam Universitas Ibn Khaldun Bogor terdapat pada motif kepuasan Program Pro 2 RRI Bogor.